Transoral robotic retropharyngeal node dissection in oropharyngeal squamous cell carcinoma: Patterns of metastasis and functional outcomes. Issue 10 (31st July 2017) - Troob, Scott; Givi, Babak; Hodgson, Macgregor; Mowery, Alia; Gross, Neil D.; Andersen, Peter E.; Clayburgh, Daniel
Abstract: Background: Assessment of the retropharyngeal lymph nodes is essential in the treatment for oropharyngeal squamous cell carcinoma (SCC). Transoral robotic retropharyngeal lymph node dissection (RPLND) may provide valuable staging information and guide selection of adjuvant therapy in a transoral robotic surgery (TORS) treatment paradigm. Methods: Outcomes were compared between 30 patients with oropharyngeal SCC with tonsillar primaries undergoing RPLND and 37 stage‐matched cases without RPLND. Results: Retropharyngeal metastasis was confirmed in 6 patients undergoing RPLND. Compared with 37 stage‐matched controls, there were no differences in length of stay, length of feeding tube dependence, net change in perioperative weight, or rates of hemorrhage and postoperative complications. RPLND altered adjuvant treatment recommendations in 1 of 30 patients. Conclusion: RPLND is technically feasible by a purely transoral robotic approach. Its performance is not associated with worse swallowing outcomes or rates of complication. In select patients, RPLND may provide valuable staging information and guide the selection of adjuvant therapy.